A randomized study to prevent lymphedema in women treated for breast cancer: CALGB 70305 (Alliance). Issue 2 (20th October 2020) - Paskett, Electra D.; Le‐Rademacher, Jennifer; Oliveri, Jill M.; Liu, Heshan; Seisler, Drew K.; Sloan, Jeffrey A.; Armer, Jane M.; Naughton, Michelle J.; Hock, Karen; Schwartz, Michael; Unzeitig, Gary; Melnik, Marianne; et al.
Abstract : Background: Lymphedema affects many women who are treated for breast cancer. We examined the effectiveness of an education‐only (EO) versus education plus sleeve compression/exercise intervention (lymphedema education and prevention [LEAP]) on lymphedema incidence and range of motion (ROM) in a group‐randomized trial across 38 cooperative group sites. Methods: The treating institution was randomly assigned to either EO or LEAP by a study statistician. All patients at a treating institution participated in the same intervention (EO or LEAP) to minimize contamination bias. Participants completed surveys, arm volume measurements, and self‐reported ROM assessments before surgery and at 12 and 18 months after surgery. Lymphedema was defined as a ≥10% difference in limb volume at any time post‐surgery up to 18 months after surgery or diagnosis by a health provider. Cochran‐Mantel‐Haenszel tests were used to compare lymphedema‐free rates between groups, stratified by lymph node surgery type. Self‐reported ROM differences were compared between groups. Results: A total of 554 participants (56% LEAP) were included in the analyses. At 18 months, lymphedema‐free rates were 58% (EO) versus 55% (LEAP) ( P = .37). ROM for both arms was greater in LEAP versus EO at 12 months; by 18 months, most women reported full ROM, regardless of group. In LEAP, only one‐third wore a sleeve ≥75% of the time; 50% performed lymphedema exercises at least weekly. Conclusion: Lymphedema incidence did not differ by intervention group at 18 months. Poor adherence in the LEAP group may have contributed. However, physical therapy may speed recovery of ROM. Further research is needed to effectively reduce the incidence and severity of lymphedema in patients who have breast cancer. Abstract : Women in an exercise plus education group (lymphedema education and prevention [LEAP]) had faster return of full range of motion, but with no difference by intervention group in lymphedema incidence at 18 months. Poor adherence in the LEAP group may have contributed to similar lymphedema rates in the intervention groups; however, physical therapy may speed recovery of range of motion.